Rebecca of Sunnybrook Farm - McFadden, Deanna; Akib, Jamel; Wiggin, Kate Douglas Smith, 1856-1923. (New York : Sterling Pub., 2007)
An abridged version of Kate Douglas Wiggin's classic story of talkative, ten-year-old Rebecca's adventures after she leaves her home at Sunnybrook Farm to go live in town with her spinster aunts, one harsh and demanding, the other soft and sentimental.
4.4
3-6
3-6
Keywords: Aunts -- Juvenile fiction; City and town life -- New England -- Juvenile fiction; Aunts -- Fiction; City and town life -- New England -- Fiction; New England -- Fiction; Aunts -- Fiction; City and town life -- New England -- Fiction; New England -- Fiction